Two new species of the genus Unaspis MacGillivray, 1921 (Hemiptera: Coccomorpha: Diaspididae) from China - Niu, Minmin; Feng, Jinian (Zootaxa, 2019)
Two new species of Unaspis (Hemiptera: Coccomorpha: Diaspididae) from China, U. menglunensis sp. n. and U. fanjingensis sp. n., are described and illustrated. A key to the world fauna species of Unaspis is provided.